Interactive Video Story Media to Improve Science and Social Studies Learning Outcomes in Elementary School - Kadek Anggi Pratiwi; Kadek Suranata; Kadek Yudiana (Journal of Education Technology, 2025)
Science and Social Studies (IPAS) learning in elementary schools continues to face challenges in engaging students and facilitating understanding of abstract concepts. The use of conventional instructional methods often results in low student participation and suboptimal learning outcomes. This study aims to develop and evaluate the effectiveness of interactive video story learning media in improving fifth-grade students’ learning outcomes in IPAS subjects. The study employed a Research and Development approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants consisted of 25 fifth-grade elementary school students. Data were collected through questionnaires and multiple-choice achievement tests and analyzed using qualitative and quantitative descriptive analysis as well as inferential statistical testing. The findings indicate that the interactive video story learning media demonstrated a very high level of validity and practicality based on evaluations by experts, teachers, and students. The effectiveness test using a one-group pretest–posttest design revealed a statistically significant improvement in students’ learning outcomes (p < 0.05). In addition to academic improvement, the use of interactive video story media enhanced students’ motivation, engagement, and active participation in the learning process. This study concludes that interactive video story learning media is effective for IPAS instruction at the elementary school level and represents an innovative, technology-based alternative for improving the quality of classroom learning.